Bralni vzori: Bralne navade strokovnih delavcev v vrtcih, šolah ter knjižnicah - Haramija, Dragica; Fras Popović, Sabina; Pečjak, Sonja; Ivanuš Grmek, Milena; Javrh, Petra; Jančič Hegediš, Polona; Jug, Tjaša; Kovač, Mihael; Licardo, Marta; Mithans, Monika; Puncer, Mojca; Šek, Polonca; et al. (2025)
Reading Role Models: The Reading Habits of Professional Staff in Kindergartens, Schools. Reading literacy develops throughout the entire life, and especially intensively in time of education. Among the key factors for the development of reading competencies and reading culture of children and young people is an adult who monitors their development and is a reading role model. First and foremost, these are parents and caretakers, but also professional educational and library workers, who are extremely important promoters of the reading habits of children, pupils, students, and other adults in the educational process. In the project Reading role models: reading habits of professional staff in kindergartens, schools, faculties, and public libraries, we will therefore focus on the study and evaluation of the meaning and role, understanding, prevalence, development and presence of reading habits of educational and library professionals. The project runs for 24 months (October 2023 - September 2025) and involves 17 researchers from the Faculty of Education, University of Maribor and the Faculty of Arts, University of Ljubljana.
Keywords: reading literacy; reading habits of teachers; reading habits of librarians; frequency of reading; quality of reading materials